2014
DOI: 10.3329/bmjk.v46i1-2.18233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intralesional bleomycin as an alternative therapy for cystic hygroma

Abstract: Bang Med J Khulna 2013; 46 : 12-15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…In our study we found that of patients who received sclerotherapy, 1 (5%) patients had received two sessions of bleomycin, 4 (20%) had received three sessions and 15 (75%) had received 4 doses of bleomycin. These results were similar to many other studies in which mostly patients received 3 to 4 sessions of bleomycin for complete resolution [13][14].…”
Section: Discussionsupporting
confidence: 91%
“…In our study we found that of patients who received sclerotherapy, 1 (5%) patients had received two sessions of bleomycin, 4 (20%) had received three sessions and 15 (75%) had received 4 doses of bleomycin. These results were similar to many other studies in which mostly patients received 3 to 4 sessions of bleomycin for complete resolution [13][14].…”
Section: Discussionsupporting
confidence: 91%
“…The mean age of patients in our study was 3.22 ± 3.39 years, youngest being 11 days and the oldest being 15 years similar to most of the reports. [ 19 20 ] Post sclerotherapy, no major injection-related event or complication occurred. Oral paracetamol was found to be effective for control of pain and fever.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure under sedation is preferred for accurate drug delivery, although we avoided intravenous sedation and managed them on an outpatient basis. [ 19 20 ] Patients were reviewed after 3 weeks for assessment of response and repeat sclerotherapy was given if deemed necessary for a maximum of four sessions.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of hemangioma remains unknown. Three phases were noted in the evolution of hemangioma namely rapid proliferating phase, involuting phase and involuted phase [3]. The clinical course, severity and complications of the condition depends on the site of occurrence of the lesion like airway obstruction, visual disturbances.…”
Section: Introductionmentioning
confidence: 99%